2017
DOI: 10.1007/s13197-017-2509-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on the gel properties of the body wall of sea cucumber (Apostichopus japonicus)

Abstract: The sensory texture of sea cucumber (Apostichopus japonicus) was dramatically affected by heat treatment. In this study, sea cucumbers were heated under different thermal conditions (HSC), and divided into five groups (HSC-80, HSC-90, HSC-100, HSC-110, and HSC-120) according to the heating temperature (from 80 to 120°C). The changes in texture, moisture, gel structure, and biochemical parameters of the HSC were investigated. With increasing heating time (from 10 to 80 min), the hardness and gel structure chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Preliminary experiments showed that 0.4% to 0.6% ( w / v ) oxidized oligosaccharides solution could provide decent stabilization to rehydrated sea cucumbers, so in this study rehydrated sea cucumbers were all heated in 0.5% oxidized oligosaccharide solutions for crosslinking. The crosslinked sea cucumbers were then heated in a sterilizer at 121 °C for 10 min, which according to our previous work [ 21 ], could result in severe deterioration to normal rehydrated sea cucumbers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary experiments showed that 0.4% to 0.6% ( w / v ) oxidized oligosaccharides solution could provide decent stabilization to rehydrated sea cucumbers, so in this study rehydrated sea cucumbers were all heated in 0.5% oxidized oligosaccharide solutions for crosslinking. The crosslinked sea cucumbers were then heated in a sterilizer at 121 °C for 10 min, which according to our previous work [ 21 ], could result in severe deterioration to normal rehydrated sea cucumbers.…”
Section: Resultsmentioning
confidence: 99%
“…Heat-promoted deterioration typically softens sea cucumber body wall and increases soluble materials, which cause serious damage to rehydrated sea cucumbers, so it is currently one of the biggest problems limiting the development of ready-to-eat products from rehydrated sea cucumbers. Our group has previously suggested that deterioration is caused by heat-promoted breakage of chemical bonds in sea cucumber collagen [ 21 ], which could be avoided by extra crosslinking. The commercial value of sea cucumber relies heavily on its unit size and integrity, so crosslinking agents have to be introduced without damaging the appearance of sea cucumbers, preferably by free diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The highest W abs was observed for SCBWs cooked for 180 min and soaked beyond 40 hr, with a value of 3.4. During heating, the collagen fibers inside SCBWs are denatured to form soluble gelatin (Zhang et al., ). The degree of collagen denaturation is likely to be dependent on the heating time, which may lead to changes in the internal structures of the SCBW (for example, change of porosity) and cause the different water absorption capacities in the SCBWs.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al. () also reported that the continuous heating of sea cucumber body wall at high temperatures breaks its internal chemical bonds, causing the decomposition of the sea cucumber collagen fibers and gel structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation